THE GROWTH AND YIELD PERFORMANCE OF TRUE SHALLOT SEED PRODUCTION IN CENTRAL SULAWESI, INDONESIA - Saidah; Wahyuni, Andi Nirma; Muchtar; Suluk Padang, Irwan; Sutardi (Asian Journal of Agriculture, 2020)
Abstract. Saidah, Wahyuni AN, Muchtar, Padang IS, Sutardi. 2020. The growth and yield performance of true shallot seed production in Central Sulawesi, Indonesia. Asian J Agric 4:  18-22. Shallot  (Allium ascalonicum L.) is a vegetable commodity that has high economic value and market prospects. So far, planting shallots using seeds from tubers, but planting onions with seeds is better and cost efficiency and seeds are healthier. The aim of this study was to determine the growth and yield performance of true shallot seed production in Central Sulawesi, Indonesia. The study was conducted from May to September 2018 in Wuasa Village, North Lore Sub-district, Poso District at an altitude of 1083.7 meters above sea level. Research with an on farm research approach on farmer's land as a cooperator covering an area of ??3000 m2. The study used the Probability Sampling Method with 10 replications. The results showed that the growth and yield performance of true shallot seed in Central Sulawesi was quite high. This is due to the suitability of the climatic conditions and cultivation technology that has been applied. In the yield component, the percentage of flowering plants was quite high at 78% with a number of capsules/flowers at 80.67. The success of true shallot seed production is expected to be able to replace the source of seed from the tuber which has been containing viruses and diseases carried by the tuber seeds.